Numismática tardía de la Región de Murcia. El conjunto de monedas del Puerto de Mazarrón (Murcia) - Lechuga Galindo, Manuel (Antigüedad y Cristianismo, 1998)
Here is a study of a new find of coins of the later Roman period (352-395 AD) from El Puerto de Mazarrón, characterised by a major presence of issues from Constance 11 and a predominance once again, of oriental mints (and Roman) rather than those from the West.